Die skeppingsordeninge en homoseksualiteit - Naudé, R. M. (Hervormde teologiese studies, 1988)
The ordination of creation and homosexuality The idea of creation ordinances is treated according to the theologies of Emil Brunner, Karl Barth and Helmut Thielicke in the light of the conjugation of the ordinance and homosexuality by Heinrich Ott on the one hand, and between the ordinance and the relation between dogmatics and ethics by Walter Kreck on the other hand. This results in the theory that the evaluation of homosexuality depends on the balanced relation between dogmatics and ethics to avoid ortodoxism and moralism.